Biodegradation of oil and grease in upflow anaerobic sludge blanket reactor for palm oil mill effluent treatment - Lee, Chee Siang (2006)
The upflow anaerobic sludge blanket (UASB) reactor is a system in which substrate passes first through an expanded sludge bed containing a high concentration of biomass. The sludge in the reactor may exist in granular or flocculent form. Most of the substrate removal takes place in sludge bed and the remaining portion of the substrate passes through a less dense biomass, sludge blanket. UASB reactor is one of the innovative high rate anaerobic digester that able to biodegrade the oil and grease (O&G) in palm oil mill effluent (POME). This study aimed to evaluate the biodegradation of O&G in raw POME using UASB. The objectives of this study were to determine the O&G biodegradation and chemical oxygen demand (COD) removal efficiencies for the treatment of POME using UASB and evaluate the UASB’s performance in relation to various control variables. The characteristic of the raw POME were determined for 5 respective samples collected from Bukit Besar, Kulai. Hexane was used as the solvent for O&G extraction by using separatory funnel. The experiments of O&G biodegradation and COD removal were designed using full factorial design. The selected factors were hydraulic retention time (HRT), influent strength based on COD and influent pH. The steady state of the UASB was achieved after 26 days acclimatization with the COD removal constant at 62%. Then, the factorial designed experiments were conducted and percentage of O&G biodegradation and COD removal as the responses. The optimum combination of operating parameters was HRT 12.9 hrs, influent 5000 mg/L COD and influent pH 7 which success to remove 61.7% COD and biodegrade 62.9% O&G. Statistical analysis was used to study the UASB’s performance in relation to various control operating parameters. The main factors that have significant effect on O&G biodegradation and COD removal were defined statistically.